Financial Performance of Indian Private Life Insurance Companies in the Post Liberalisation Period: A Comparative Study between the First Two Decades of 21st Century - Das Sharma, Debashis; Chandra Sarkar, Subhas (Management Journal for Advanced Research, 2023)
Insurance sector in India played a vibrant role in the development of economy. At the advent of new economic policy in 1991, insurance sector has started dynamic changes following the slogan of LPG. IRDA was formed as regulatory authority in 1993, to monitor and control over the insurance market. There was only public sector insurance company in the Indian life insurance business popularly known as LIC who have enjoyed monopoly from 1956 to 1999 over the life insurance sector. This scenario has dramatically changed after the entry of 23 private life insurance players with joint venture of Indian companies in 1st decade of 21st century. These companies have introduced several dynamic business strategies to capture the market within a very short period of time. Innovative products, smart marketing and aggressive distribution have enabled fledgling private insurance companies to get Indian customers to sign up faster than anyone expected. A healthy competitive environment has been observed during this period. Private insurers snatched a significant portion of the market share within couple of years. Life insurance industry observed remarkable growth and development in the post liberalisation period. An attempt has been made to evaluate the financial performance of the selected private life insurers between the first and 2nd decade of 21st Century. The objective of the study is to examine whether financial performance of the private life insurance companies have been improved from 1st decade to 2nd decade. With a view to attaining the objectives financial performance have been measured by using selected ratios of CARAMEL framework. Six indicators have been used to assess the Capital adequacy, Asset quality, Reinsurance & actuarial issues, management soundness, Earnings and profitability and Liquidity position of the companies. With a view to comparative analysis Mean and CV of the selected ratios of each companies have been tabulated during the two decades. The results obtained are statistically tested with the help of paired sample t-test in order to draw the logical inferences. It has been observed that financial performance of most of the private life insurance companies have been improved from 1st decade to 2nd decade.